Determinants of Firm Growth with Sales as an Intervening Variable in the Sharia Economic Perspective in the Garment Industry in East Java - Dedy Triyono; Aminullah Assagaf; Liosten Rianna Roosida Ully Tampubolon (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
The garment industry in East Java faces various challenges such as increasing market competition, the emergence of substitute products, changes in consumer lifestyles, and the development of digital technology that influence business strategies and firm growth. This study aims to analyze the effects of competitors, substitute products, product innovation, digital marketing, social media, lifestyle, and consumer preferences on firm growth with sales as an intervening variable from a Sharia economic perspective. The study employed a quantitative approach using a survey method involving 377 garment business actors in East Java. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that competitors, digital marketing, lifestyle, and consumer preferences have a significant effect on sales. Meanwhile, competitors, substitute products, digital marketing, lifestyle, and consumer preferences significantly influence firm growth. Product innovation and social media do not have a significant effect on either sales or firm growth. Sales are also unable to mediate the relationship between strategic factors and firm growth. These findings indicate that digital strategies, an understanding of consumer lifestyles, and the company’s ability to respond to market preferences are important factors in driving the growth of garment companies in East Java.